IDENTITY CRISIS AND NATION BUILDING IN NIGERIA - Inyokwe, Otinche Sunday (EBSU Journal of Social Sciences and Humanities, 2022)
The identity crisis in Nigeria is a product of colonialism nurtured by the post- colonial elites for selfish ends. Elements of progressive social engineering among the diverse ethnic groups were undermined in the formative years of the Nigerian state. State building takes precedence over nation building even when the philosophical elements of nationhood like commonality of culture, language, and tradition were lacking. These elements are instruments of political and social mobilization for the development of liberal democratic polity. The adverse relation among these elements forms the basis of identity crisis confronting the Nigerian state. However, it is ironical to continue to put the blame of the identity crisis and citizenship question on the doorstep of the colonial masters after 51 years of independence. Political alienation and political domination which was the dominant feature of colonial administration has been made the deciding factor in economic and socio-political relations. This has foreclosed attempts to develop appropriate political framework for the effective management of the citizenship question in Nigeria. The result is unhealthy competition for limited but scarce resources giving rise to dissension within and among indigenes and settlers. The attendant crisis is manifestation of poverty and political and economic inequality. This has limited the right to political participation for the disadvantaged group. This paper relied on primary and secondary data to conclude that the attendant identity crisis is against the norms of co-operative federalism, democracy, sustainable development and good governance. The paper recommends the distribution of national resources on the basis of equity, a national and cultural orientation that promote inter and intra-ethnic harmony as panacea to reviving the oblivious social capital in Nigeria among others.